Intuitionistic Preference Modeling and Interactive Decision Making - Xu, Zeshui (Studies in Fuzziness and Soft Computing, 2014)
This book offers an in-depth and comprehensive introduction to the priority methods of intuitionistic preference relations, the consistency and consensusÂ improving procedures for intuitionistic preference relations, the approaches to group decision making based on intuitionistic preference relations, the approaches and models for interactive decision making with intuitionistic fuzzy information, and the extended results in interval-valued intuitionistic fuzzy environments.